(3eaGJjM GdTQGFYs - (3GdcGTj Ch GdcGTGfj, GdeJCdg GdMcje, eMSf Hf eQJVi Hf ajV Gddg eMehO, J (B1090 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3af GdYHGOGJ hGdeYGedGJ ef cJGH eaGJjM GdTQGFY hajg cJH eaGJjM GdeWGYe hGdeTGQH eaGJjM GdefGcM hGdehGdjO eaGJdjM GdeYGjT hGdecGSj eaGJjM GdYWGjG hGdeQhI (B....s
(3BNQgG (B:s
.. (3hjSei gfG HLQ GdLQ adh de jbd HGdGfLQGQ Edi LO aeGJ (B...(3aj GdOjf ceG aj GdNHQ GdeTghQ haj Gdbhi cd TjA eWdb MJi hQO gPG BNQ eaGJjM (B.s
(3JHUQI GdeDda (B:s
(3jbhd GdRQcdj (B: (3hQO GSeg (B" (3eMSf Hf eQJVi (B" (3h (B" (3eMSf Hf eMqeO (B" (3h (B" (3eMeO eMSf (B" (3hbjd dg (B" (3GdajV (B" (3hYQa LOg HajV Gddg hHGdajV(B. (3hLGAJ fSHJg (B" (3GdcGTj (B" (3h (B" (3GdcGTGfj (B" (3h (B" (3GdbGTGfj (B" (3hjbGd dg(B: (3edG eMSf ajV GdcGTjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\290s
(3EjVGM Gdecfhf (B2\521s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis